2016
DOI: 10.1063/1.4964654
|View full text |Cite
|
Sign up to set email alerts
|

Development of an interatomic potential for the simulation of defects, plasticity, and phase transformations in titanium

Abstract: New interatomic potentials describing defects, plasticity, and high temperature phase transitions for Ti are presented. Fitting the martensitic hcp-bcc phase transformation temperature requires an efficient and accurate method to determine it. We apply a molecular dynamics method based on determination of the melting temperature of competing solid phases, and Gibbs-Helmholtz integration, and a lattice-switch Monte Carlo method: these agree on the hcp-bcc transformation temperatures to within 2 K. We were able … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 52 publications
7
55
0
3
Order By: Relevance
“…The formation of ω-phase in Ti, Zr, and Hf, and their alloys have attracted much theoretical work and computer simulations [3,7,10,[55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Already in 2001, Greef et al performed the first-principles electronic structure calculations and constructed the equilibrium free energies for the α-and ω-phases in Ti [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of ω-phase in Ti, Zr, and Hf, and their alloys have attracted much theoretical work and computer simulations [3,7,10,[55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Already in 2001, Greef et al performed the first-principles electronic structure calculations and constructed the equilibrium free energies for the α-and ω-phases in Ti [55].…”
Section: Discussionmentioning
confidence: 99%
“…The crystallographic mechanism of the α ↔ ω (or α ↔ β ↔ ω) phase transformation was described in Reference [3] as being based on two possible orientation relationships: OR 1 (0001) α (0111) ω ; 1120 α 1101 ω and OR 2 (0001) α (1120) ω ; 1120 α 0001 ω . However, the using of different pseudopotentials to represent titanium (such as those of Ackland, Mishin, Kim or Hennig) can lead to the significant differences in the calculation results [56][57][58]. Thus, the apparently arbitrary choices in the reference configuration can lead to significant differences in the calculated quantities [56].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy has been discussed in previous publications [19,29]. In recent work it has been shown that this potential fitting procedure can be improved by including basal faults in the set of fitting parameters with the inclusion longer ranged interactions [30].…”
Section: The Basal γ-Surfacementioning
confidence: 90%
“…Secondly, we develop the most accurate MLIP of the elemental Ti ever reported using a linearized MLIP framework. As shown later, the high accuracy of [10][11][12][13] and MEAM [14][15][16][17] potentials. Some of these curves are obtained from the interatomic potential repository project [18] and KIM project [19].…”
mentioning
confidence: 99%